Efektivitas penggunaan POC kotoran ayam metode brewing dan pupuk kandang sapi terhadap pertumbuhan dan produksi sawi hijau - Rahma aulia; Fedri Ibnusina; Walmadri (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Green mustard (Brassica juncea L.) is a horticultural commodity with high economic value and nutritional content, but its productivity is still constrained by low soil fertility and heavy reliance on inorganic fertilisers. The use of Liquid Organic Fertiliser (POC) from chicken waste using the brewing method combined with cow manure is expected to be an alternative in increasing plant growth and production sustainably. This study aims to determine and analyse the effect of providing POC from chicken waste using the brewing method and cow manure on the growth and production of green mustard. The study was an experimental method with a Randomised Block Design (RBD) consisting of 4 treatments and 6 replications. The treatments given included P0 (100% NPK), P1 (POC 250 ml/l + cow manure 10 tons/ha), P2 (POC 500 ml/l + cow manure 10 tons/ha), and P3 (POC 750 ml/l + cow manure 10 tons/ha). Data analysis used the ANOVA test at the probability error level = 0.05, and further testing using the 5% DMRT test. The results showed that the 100% NPK treatment produced the highest values for most growth and yield parameters. Among the organic fertiliser treatments, the application of 250 mL L⁻¹ chicken manure-based LOF produced by the brewing method combined with 10 t ha⁻¹ cow manure showed the most favourable growth and yield response. Therefore, this treatment is recommended as the best organic fertilization treatment tested in this study, although its performance remained lower than that of the 100% NPK treatment.